Gambling and financial markets a comparison from a regulatory perspective - Weidner, Linus (Frontiers in Sociology, 2022)
This article discusses similarities between the finance industry and the gambling industry. It considers empirical studies from both fields and compares both industries with regard to possible substitution effects. Afterwards, the current regulatory approach to gambling and financial markets is discussed. Based on this literature review, the author points out that regulators need to acknowledge the fact that both markets possess addictive properties and attract certain risk-seeking individuals. Moreover, the regulators need to find a way to align their fundamentally different objectives to find common solutions to cross-industry problems. Finally, an increased cooperation between (state) authorities is necessary. This cooperation could help to protect traders from developing gambling-related problems, provide significant insights for industry-wide and product-specific regulation and lead to a more informed use of technology for harm prevention purposes. The most important similarities and differences of both markets and the resulting regulatory implications are briefly summarized.